“The Instant Vegan” - Dibb, Kelly (The IIE, 2022)
This research study has investigated the influence that Instagram has on millennials dietary choices when becoming vegan. Identifying the various factors that help contribute to influencing millennials decisions and persuading them to change their lifestyle was beneficial as it will be able to allow brands to see how they can use various marketing tools to influence people to buy their products or use their services. The research followed a qualitative approach and used online interviews as well as online surveys to collect the relevant data needed for this study. Covid-19 did prevent physical interaction with participants throughout the research, however, the findings that were gathered were conclusive. This study contributes towards a deeper understanding of how the world is changing and how social media applications such as Instagram are being used for millennial to compare themselves to one another and change their lifestyle choices based on the information and visuals they are exposed to on Instagram.
Keywords: Veganism; Millennials; Instagram; Lifestyle; Marketing